Curtain fabric with antibacterial function and preparation method thereof

By using composite antibacterial agents loaded with nanosilver and OPHB bio-based antibacterial stock solution, the existing antibacterial curtain fabric has been solved, and efficient and lasting antibacterial effect is achieved, while reducing the cost of use.

CN119189438BActive Publication Date: 2025-04-18SHAOXING XIAOXUANCHUANG FABRIC CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411731832.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-04-18
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

Existing antibacterial curtain fabrics have challenges in the high cost and the lack of lasting antibacterial effects, and it is difficult to meet the market's demand for a healthier and safer indoor environment.

Method used

The composite antibacterial agent with nanosilver-loaded composite modified titanium dioxide particles and OPHB bio-based antibacterial stock solution is used to enhance the dispersion and binding of the antibacterial agent to form a long-lasting antibacterial layer by modifying the polyethyleneimine and silane coupling agent.

Benefits of technology

With the addition of a small amount of antibacterial agent, the antibacterial performance and durability of curtain fabrics are significantly improved, the use of silver ions is reduced, the cost is reduced, and the problem of single antibacterial agent failure due to long-term use is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application relates to the field of textiles, and specifically discloses a curtain fabric with antibacterial function and a preparation method thereof. The curtain fabric comprises a base fabric layer, an antibacterial layer and a surface layer, wherein the antibacterial layer is formed by applying an antibacterial agent on the surface of the base fabric layer, and the antibacterial agent at least comprises composite modified titanium dioxide particles loaded with nano-silver and OPHB bio-based antibacterial stock solution; wherein the modified titanium dioxide particles are prepared by loading nano-silver on titanium dioxide and then modifying titanium dioxide with polyethyleneimine and a silane coupling agent; the preparation method comprises the following steps: applying an antibacterial agent on the surface of the base fabric layer, and then drying to form an antibacterial layer; laminating and hot-pressing the side of the base fabric layer formed with the antibacterial layer to the surface layer to prepare the curtain fabric with antibacterial function. The present application has the characteristics of preparing curtain fabric with good antibacterial effect, while reducing costs and improving antibacterial durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of textiles, and more specifically, to a curtain fabric with antibacterial function and a preparation method thereof. Background Art

[0002] Curtains, as part of home decoration, not only have the function of blocking light and protecting privacy, but also can add beauty to the interior. However, curtains can easily become a breeding ground for bacteria and mold. In special periods, such as epidemics or seasonal colds, curtains may become a potential medium for the spread of bacteria.

[0003] As people's health awareness improves and the requirements for living environment increase, the market demand for textiles with antibacterial functions continues to grow. In order to create a healthier and safer indoor environment, antibacterial curtains came into being.

[0004] One of the biggest advantages of antimicrobial curtains is that they can inhibit the growth of bacteria and mold. These microorganisms are often hidden in the fibers of the curtains and are difficult to detect with the naked eye, but they may cause poor indoor air quality and health problems. Antimicrobial curtains effectively reduce the growth of these microorganisms by releasing antimicrobial agents, making the indoor environment cleaner. Under the protection of antimicrobial curtains, the concentration of bacteria and mold in the indoor air is greatly reduced, which is especially important for those who are sensitive to allergens.

[0005] At present, antibacterial curtain fabrics are mainly curtain fabrics that have been treated with silver ion antibacterial agents or other fabric antibacterial agents through spraying, padding or dipping processes. However, this method requires the addition of a large amount of silver particle antibacterial agents, which is costly and gradually loses its effectiveness over time and use, and its durability needs to be improved.

[0006] It is necessary to provide a new technical solution for antibacterial curtain fabrics, which can reduce costs while maintaining their antibacterial effects, and also have a more lasting antibacterial effect, which is of great significance to the development of the textile materials field. Summary of the invention

[0007] In order to produce curtain fabric with good antibacterial effect, reduce cost and improve antibacterial durability, the present application provides a curtain fabric with antibacterial function and a preparation method thereof.

[0008] In the first aspect, the present application provides a curtain fabric with antibacterial function, which adopts the following technical solution:

[0009] A curtain fabric with antibacterial function comprises a base antibacterial layer and a surface layer, wherein the antibacterial layer is made of a blend of polyester fiber and cotton fiber and coated with an antibacterial agent, wherein the antibacterial agent at least comprises composite modified titanium dioxide particles loaded with nano-silver and OPHB bio-based antibacterial stock solution; wherein the modified titanium dioxide particles are made of titanium dioxide loaded with nano-silver and then modified with polyethyleneimine and a silane coupling agent.

[0010] By adopting the above technical scheme, the antibacterial agent in this application is selected from the composite of composite modified titanium dioxide particles and OPHB bio-based antibacterial stock solution. OPHB bio-based antibacterial stock solution is a natural bio-based antibacterial agent with the characteristics of safety, environmental protection and non-toxicity. It can effectively inhibit the growth and reproduction of bacteria, and synergize with nano-silver and modified titanium dioxide particles to enhance the overall antibacterial properties of curtain fabrics. More importantly, the antibacterial agent in this application is mainly composite modified titanium dioxide particles loaded with nano-silver. Nano-silver has a spectrum of antibacterial properties and can effectively kill or inhibit the growth of a variety of bacteria, viruses and fungi. In addition, nano-silver has many opportunities to contact with microbial cell walls and has a good antibacterial effect. More importantly, nano-silver particles continuously release silver ions on the surface of the fabric. When the bacterial cells lose their activity, the silver ions will be freed from the cells and repeat the sterilization activity, so that a more lasting antibacterial effect can be obtained.

[0011] Titanium dioxide itself has photocatalytic antibacterial properties and can decompose organic matter and kill bacteria under light conditions. The main components of bacterial cell walls are peptidoglycan and teichoic acid, which will dissociate and carry negative charges under neutral conditions. Therefore, the surface of bacterial cells is usually negatively charged. Therefore, in this application, positively charged polymer polyethyleneimine is used as a surface modifier for titanium dioxide, which can be evenly wrapped on the surface of titanium dioxide particles. The positively charged modifier and the negatively charged microbial cell wall produce electrostatic attraction, thereby increasing the contact opportunity between titanium dioxide particles and microorganisms. In addition, the presence of the modifier can also improve the dispersibility and stability of titanium dioxide particles in water. It is beneficial to the dispersion of modified titanium dioxide particles in the antibacterial agent, and can be more evenly coated on the matrix layer to achieve better antibacterial effect. More importantly, the addition of positively charged polyethyleneimine enables the modified titanium dioxide particles to produce electrostatic attraction with microbial cells through the positive charge on their surface even in the absence of light, thereby inhibiting the growth and reproduction of microorganisms. The addition of silane coupling agent reacts with the hydroxyl groups on the surface of titanium dioxide particles to form a modified layer to enhance the chemical bonding between titanium dioxide and polyethyleneimine. It can also enhance the bonding force between titanium dioxide and base fabric fibers to prevent them from falling off or failing, thereby achieving more lasting antibacterial properties.

[0012] Finally, the antibacterial agent in this application utilizes the multi-faceted antibacterial effects of photocatalysis, nanosilver and bio-based materials, which can achieve excellent antibacterial effects with a small amount of antibacterial agent added, reduce the addition of silver ions, and reduce costs. Moreover, the antibacterial agents can form a synergistic effect to prevent a single antibacterial agent from becoming ineffective due to long-term use, and can achieve a more lasting antibacterial effect.

[0013] Optionally, the composite modified titanium dioxide particles loaded with nanosilver are prepared by the following method:

[0014] 1) Mixing silver chloride solution and polyvinyl pyrrolidone to prepare a matrix solution;

[0015] 2) Add hydroxypropyl cellulose, glutathione and titanium dioxide to the base solution and stir to obtain a mixture A;

[0016] 3) Adjusting the pH value of the mixture A to be alkaline, and adding glucose reducing agent to the mixture A to react, so that the silver chloride is reduced to nano-silver loaded on the titanium dioxide, and then centrifuging and washing with water to obtain primary modified titanium dioxide particles loaded with nano-silver;

[0017] 4) Disperse the prepared primary modified titanium dioxide particles in 3-4 times the mass of water, add polyethyleneimine, stir for 1-2 hours, then drop silane coupling agent, stir for 2-3 hours, centrifuge, wash with water and dry to obtain composite modified titanium dioxide particles loaded with nanosilver.

[0018] By adopting the above technical scheme, in the present application, silver chloride is used as the nano-silver raw material, glucose is used as a reducing agent, silver chloride is reduced to nano-silver under alkaline conditions, polyvinyl pyrrolidone is used as a stabilizer, and hydroxypropyl cellulose is used as an anti-settling agent to prevent the sedimentation of titanium dioxide, thereby facilitating the uniform loading and dispersion of the generated nano-silver on the surface of titanium dioxide, and glutathione is used as the dispersion stability of titanium dioxide and nano-silver, and its sulfhydryl group can form a chelating effect with the surface of titanium dioxide and adsorb on the surface of titanium dioxide particles, thereby preventing the mutual agglomeration between particles, and forming a certain steric hindrance effect, which can further prevent the agglomeration of particles. Similarly, the generated nano-silver has the same steric hindrance effect, which not only helps the dispersibility and stability of titanium dioxide in the suspension and prevents precipitation or aggregation, but also has a certain dispersing effect on the nano-silver, thereby improving the uniform loading and dispersion of the nano-silver on the surface of titanium dioxide.

[0019] Optionally, when preparing composite modified titanium dioxide particles loaded with nano-silver, the amount of polyvinyl pyrrolidone added in step 1) is 1-3wt% of the silver chloride solution, and the mass concentration of silver chloride is 45-50%;

[0020] In step 2), the mass ratio of hydroxypropyl cellulose to glutathione is 1:(1.2-1.5), and the amount of hydroxypropyl cellulose added is 0.5-1.5wt% of the matrix solution, and the mass ratio of titanium dioxide to silver chloride added is 1:(1.5-2);

[0021] In step 3), the mass ratio of glucose to silver chloride added is 1:(1.8-2.5);

[0022] In step 4), the amount of polyethyleneimine added is 3-5wt% of the primary modified titanium dioxide particles, and the amount of silane coupling agent added is 1-3wt% of the primary modified titanium dioxide particles.

[0023] By adopting the above technical solution and controlling the above addition amount, the silver chloride is more evenly dispersed and loaded on the titanium dioxide.

[0024] Optionally, when preparing composite modified titanium dioxide particles loaded with nanosilver, tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is added together with glutathione, and the added amount of tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is 0.05-0.1wt% of titanium dioxide.

[0025] By adopting the above technical solution, when a small amount of tetramethylammonium bis(trifluoromethanesulfonyl)imide salt ionic liquid is added in the present application, it is found that its cations can accept electrons on the conduction band of titanium dioxide, and the anions can transfer holes to the valence band of titanium dioxide, thereby effectively inhibiting the recombination of electron-hole pairs, and more effectively promoting the separation and antibacterial effect of photogenerated electron-hole pairs, and its combined action with glutathione can further enhance the stability and dispersibility of nanosilver and titanium dioxide.

[0026] Optionally, the titanium dioxide is prepared by the following method:

[0027] A mixed solution of titanium tetrachloride and zinc chloride is added into ammonia water to obtain titanium dioxide colloidal particles, and then PEO is added and stirred and mixed, and then aged at 60-80°C, and then washed with a buffer solution and dried, and then calcined at high temperature to obtain porous titanium dioxide.

[0028] By adopting the above technical scheme, in the present application, a mixed solution of titanium tetrachloride and zinc chloride is first added into ammonia water, titanium tetrachloride is used as a raw material, zinc chloride is used as a doping metal salt, and ammonia water is used as a precipitant. First, titanium tetrachloride is hydrolyzed to generate titanium hydroxide or titanic acid, and zinc chloride generates zinc hydroxide and ammonia zinc ions. The above products form colloidal particles in the solution, and then polyethylene oxide is added and aged to make the generated colloidal particles further grow and stabilize, and at the same time, the diffusion and exchange of titanium and zinc ions in the solution are promoted to form zinc-doped titanium dioxide colloid, and then high-temperature calcination is performed. Under high-temperature calcination, the colloidal particles The organic matter PEO will be decomposed and removed, and titanium hydroxide and titanic acid will be converted into titanium dioxide. During the process, with the increase of temperature and the extension of time, the crystal form of titanium dioxide changes from amorphous or low crystallinity to high crystallinity. At the same time, the pore structure generated by the decomposition of organic matter and the release of gas makes titanium dioxide porous, and zinc hydroxide and ammonia zinc ions also generate zinc oxide under high-temperature calcination. At the same time, ammonia and zinc ions release ammonia and water vapor in the process of generating zinc oxide, which further adjusts the pore structure of titanium dioxide, and finally obtains zinc oxide-doped porous titanium dioxide with richer pore structure.

[0029] The doped zinc oxide crystals have a network effect and can provide an efficient transmission path for antibacterial ions. The porous titanium dioxide has a better loading effect on nanosilver and can also achieve sustained release of nanosilver through the pore structure. At the same time, by doping zinc oxide, an efficient transmission path is provided, so that the final fabric has a high-efficiency antioxidant effect and better antibacterial and lasting performance.

[0030] Optionally, when preparing titanium dioxide, the mass ratio of titanium tetrachloride to zinc chloride is 1:(0.3-0.5), the mass concentration of titanium tetrachloride is 20-30%, and the amount of ammonia added is 1-2 times the mass of titanium tetrachloride, and the amount of PEO added is 3-5wt% of titanium tetrachloride.

[0031] Optionally, when preparing titanium dioxide, the high temperature calcination parameters are:

[0032] First, the porous titanium dioxide is prepared by treating the porous titanium dioxide at 120-140°C for 20-40 minutes, then heating to 580-620°C for 1-2 hours, then heating to 750-800°C for 2-3 hours, then treating the porous titanium dioxide at 620-650°C for 1-2 hours, and then rapidly cooling the porous titanium dioxide.

[0033] By adopting the above technical solution and the above high-temperature calcination treatment parameters, the pore structure of titanium dioxide is more abundant, and the antibacterial fabric finally obtained has better antibacterial properties and antibacterial durability.

[0034] Optionally, the antibacterial agent is prepared by the following method:

[0035] Firstly, the OPHB bio-based antibacterial stock solution and ethanol are mixed to prepare solution A;

[0036] Adding composite modified titanium dioxide particles loaded with nanosilver into water, then adding polyvinyl alcohol and povidone, stirring and mixing, and then adding hydroxypropyl β-cyclodextrin, and mixing to prepare solution B;

[0037] Solution A is added to solution B, and the mixture is heated to 65-70°C, stirred and mixed, and then cooled to room temperature to obtain an antibacterial agent.

[0038] By adopting the above technical scheme, the OPHB bio-based antibacterial stock solution of the present application is mainly composed of oligohydroxybutyrate, which is first mixed with ethanol and then added to an aqueous solution. The addition of polyvinyl alcohol helps to increase the bonding strength between the antibacterial agent and the fiber base layer. The addition of povidone and hydroxypropyl β-cyclodextrin, especially hydroxypropyl β-cyclodextrin, has a lipophilic cavity and a hydrophilic shell, which can achieve the coating of the active ingredients of the oily OPHB bio-based antibacterial stock solution in solution A, thereby improving the compatibility and uniform dispersion of the OPHB bio-based antibacterial stock solution with the aqueous phase. When applied to the substrate, the two effective substances are more evenly dispersed, which can achieve better antibacterial performance.

[0039] Optionally, during the preparation of the antibacterial agent, each raw material is added according to the following weight parts:

[0040] 10-20 parts of OPHB bio-based antibacterial stock solution, 40-50 parts of composite modified titanium dioxide particles loaded with nano-silver, 5-8 parts of polyvinyl alcohol, 3-8 parts of povidone, 8-15 parts of hydroxypropyl beta-cyclodextrin, 30-40 parts of ethanol, and 50-70 parts of water.

[0041] Optionally, the surface layer is made of pure cotton fabric, linen fabric, polyester fabric or blended fabric.

[0042] By adopting the above technical solution, the base fabric of the antibacterial layer in the present application is a blended fabric of polyester fiber and cotton fiber, which has good strength and air permeability, while the surface fabric can be selected according to the application scenario and preference.

[0043] In a second aspect, the present application provides a method for preparing a curtain fabric with antibacterial function, using the following technical solution:

[0044] A method for preparing a curtain fabric with antibacterial function comprises the following steps:

[0045] S1, blending polyester fiber and cotton fiber in a mass ratio of 6:(3-5) to obtain a base fabric layer;

[0046] S2, applying an antibacterial agent on the surface of the base fabric layer, and then drying to form an antibacterial layer, wherein the amount of the antibacterial agent applied is 1.5-3wt% of the antibacterial base fabric;

[0047] S3, laminating the side of the base fabric layer with the antibacterial layer to the surface layer and hot-pressing them to obtain a curtain fabric with antibacterial function.

[0048] By adopting the above technical solution and selecting the application amount in the present application, the amount added is less while ensuring better antibacterial performance and antibacterial durability, which is safer and reduces costs.

[0049] Optionally, before applying the antibacterial agent to the base fabric layer in step S2, the base fabric layer is first immersed in an antibacterial liquid and then dried to obtain a pretreated base fabric layer, wherein the antibacterial liquid includes a mixed solution of an antibacterial agent, sodium dodecylbenzene sulfonate, piroctone olamine salt and water in a mass ratio of 1: (0.1-0.2): (2-3): (8-10), and then the antibacterial agent is applied to the pretreated base fabric layer to form an antibacterial layer.

[0050] By adopting the above technical scheme, in the present application, piroctone ethanolamine salt is first added as an antibacterial enhancer on the basis of the antibacterial agent, and the prepared antibacterial liquid is first impregnated to allow the antibacterial components to fully penetrate into the fiber fabric to form a deeper antibacterial layer. After the impregnation treatment, an antibacterial layer is then applied to form a layer, so that even if the outer antibacterial layer is affected by wear and tear, the internal antibacterial layer can still function, further improving the antibacterial durability.

[0051] In summary, this application has the following beneficial effects:

[0052] 1. The antibacterial agent in this application is a composite of composite modified titanium dioxide particles and OPHB bio-based antibacterial stock solution. OPHB bio-based antibacterial stock solution is a natural bio-based antibacterial agent that is safe, environmentally friendly and non-toxic. It can effectively inhibit the growth and reproduction of bacteria, and synergizes with nano-silver and modified titanium dioxide particles to enhance the overall antibacterial properties of curtain fabrics.

[0053] 2. In the present application, the positively charged polymer polyethyleneimine is used as a surface modifier for titanium dioxide, which can be evenly wrapped on the surface of titanium dioxide particles. The positively charged modifier generates electrostatic attraction with the negatively charged microbial cell wall, thereby increasing the contact opportunity between titanium dioxide particles and microorganisms. Moreover, the addition of positively charged polyethyleneimine enables the modified titanium dioxide particles to generate electrostatic attraction with microbial cells through the positive charge on their surface even in the absence of light, thereby inhibiting the growth and reproduction of microorganisms. The addition of silane coupling agent acts on the surface hydroxyl groups of titanium dioxide particles to form a modified layer to enhance the chemical bonding between titanium dioxide and polyethyleneimine. Moreover, it can also enhance the bonding force between titanium dioxide and base fabric fibers to prevent them from falling off or failing, thereby exerting a more lasting antibacterial property.

[0054] 3. The antibacterial agent in this application utilizes the multi-faceted antibacterial effects of photocatalysis, nanosilver and bio-based agents, and can achieve excellent antibacterial effects with a small amount of antibacterial agent added, reducing the addition of silver ions and reducing costs. Moreover, the synergistic effect of the antibacterial agents can be formed to prevent the failure of a single antibacterial agent due to long-term use, and can achieve a more lasting antibacterial effect.

[0055] 4. In the present application, piroctone ethanolamine salt is first added to the antibacterial agent as an antibacterial synergist, and the prepared antibacterial liquid is first impregnated to allow the antibacterial components to fully penetrate into the fiber fabric to form a deeper antibacterial layer. After the impregnation treatment, an antibacterial layer is then applied to form a layer, so that even if the outer antibacterial layer is affected by wear and tear, the inner antibacterial layer can still function, further improving the antibacterial durability. DETAILED DESCRIPTION

[0056] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0057] The OPHB bio-based antibacterial stock solution in this application is the OPHB bio-based antibacterial stock solution produced by Nanjing Hesu Times Biotechnology Co., Ltd.

[0058] The following preparation examples are preparation examples of antibacterial agents:

[0059] Preparation Example 1

[0060] A method for preparing an antibacterial agent comprises the following steps:

[0061] Step a, preparing composite modified titanium dioxide particles loaded with nanosilver, specifically comprising the following steps:

[0062] 1) Mixing a silver chloride solution having a mass concentration of 48% with polyvinyl pyrrolidone, wherein the amount of polyvinyl pyrrolidone added is 2wt% of the silver chloride solution, to obtain a matrix solution;

[0063] 2) Add hydroxypropyl cellulose, glutathione and titanium dioxide (particle size of 3-5 μm) to the matrix solution, stir and prepare a mixture A, wherein the mass ratio of hydroxypropyl cellulose to glutathione is 1:1.3, and the amount of hydroxypropyl cellulose added is 1wt% of the matrix solution, and the mass ratio of titanium dioxide to silver chloride added is 1:1.8;

[0064] 3) Adjust the pH value of the mixture A to 8.5, and add glucose reducing agent to the mixture A, the mass ratio of glucose to silver chloride is 1:2, and react at 50°C for 2h, so that the silver chloride is reduced to nano-silver loaded on the titanium dioxide, and then centrifuge and wash with water to obtain primary modified titanium dioxide particles loaded with nano-silver;

[0065] 4) Disperse the prepared primary modified titanium dioxide particles in 3.5 times the mass of water, add polyethyleneimine, stir for 1-2 hours, then drop silane coupling agent 3-(triethoxysilyl)propyl methacrylate, stir for 2.5 hours, centrifuge, wash and dry to obtain composite modified titanium dioxide particles loaded with nanosilver, the amount of polyethyleneimine added is 3.5wt% of the primary modified titanium dioxide particles, and the amount of silane coupling agent added is 1-3wt% of the primary modified titanium dioxide particles;

[0066] Step b, firstly, 15 g of OPHB bio-based antibacterial stock solution was mixed with 35 g of ethanol to prepare solution A;

[0067] Step c, adding 45 g of the composite modified titanium dioxide particles loaded with nanosilver prepared in step a to 60 g of water, then adding 6 g of polyvinyl alcohol and 6 g of povidone, stirring and mixing, and then adding 12 g of hydroxypropyl β-cyclodextrin, mixing to prepare solution B;

[0068] Step d, adding solution A to solution B, heating to 68° C., stirring and mixing, and then cooling to room temperature to obtain an antibacterial agent.

[0069] Preparation Example 2

[0070] A method for preparing an antibacterial agent comprises the following steps:

[0071] Step a, preparing composite modified titanium dioxide particles loaded with nanosilver, specifically comprising the following steps:

[0072] 1) Mixing a silver chloride solution with a mass concentration of 45% with polyvinyl pyrrolidone, wherein the amount of polyvinyl pyrrolidone added is 1wt% of the silver chloride solution, to obtain a matrix solution;

[0073] 2) Add hydroxypropyl cellulose, glutathione and titanium dioxide (particle size of 3-5 μm) to the matrix solution, stir and prepare a mixture A, wherein the mass ratio of hydroxypropyl cellulose to glutathione is 1:1.2, and the amount of hydroxypropyl cellulose added is 0.5wt% of the matrix solution, and the mass ratio of titanium dioxide to silver chloride added is 1:1.5;

[0074] 3) Adjust the pH value of the mixture A to 8, and add glucose reducing agent to the mixture A, the mass ratio of glucose to silver chloride is 1:1.8, react at 45°C for 3h, so that the silver chloride is reduced to nano-silver loaded on the titanium dioxide, and then centrifuge and wash with water to obtain primary modified titanium dioxide particles loaded with nano-silver;

[0075] 4) Disperse the prepared primary modified titanium dioxide particles in 3 times the mass of water, add polyethyleneimine, stir for 1 hour, then drop silane coupling agent 3-(triethoxysilyl)propyl methacrylate, stir for 2 hours, centrifuge, wash and dry to obtain composite modified titanium dioxide particles loaded with nanosilver, the amount of polyethyleneimine added is 3wt% of the primary modified titanium dioxide particles, and the amount of silane coupling agent added is 1wt% of the primary modified titanium dioxide particles;

[0076] Step b, firstly, 10 g of OPHB bio-based antibacterial stock solution was mixed with 30 g of ethanol to prepare solution A;

[0077] Step c, adding 40 g of the composite modified titanium dioxide particles loaded with nanosilver prepared in step a to 50 g of water, then adding 5 g of polyvinyl alcohol and 3 g of povidone, stirring and mixing, and then adding 8 g of hydroxypropyl β-cyclodextrin, and mixing to prepare solution B;

[0078] Step d, adding solution A to solution B, heating to 65° C., stirring and mixing, and then cooling to room temperature to obtain an antibacterial agent.

[0079] Preparation Example 3

[0080] A method for preparing an antibacterial agent comprises the following steps:

[0081] Step a, preparing composite modified titanium dioxide particles loaded with nanosilver, specifically comprising the following steps:

[0082] 1) Mixing a silver chloride solution with a mass concentration of 50% with polyvinyl pyrrolidone, wherein the amount of polyvinyl pyrrolidone added is 3wt% of the silver chloride solution, to obtain a matrix solution;

[0083] 2) Add hydroxypropyl cellulose, glutathione and titanium dioxide (particle size of 3-5 μm) to the matrix solution, stir and prepare a mixture A, wherein the mass ratio of hydroxypropyl cellulose to glutathione is 1:1.5, and the amount of hydroxypropyl cellulose added is 1.5wt% of the matrix solution, and the mass ratio of titanium dioxide to silver chloride added is 1:2;

[0084] 3) Adjust the pH value of the mixture A to 8.5, and add glucose reducing agent to the mixture A, the mass ratio of glucose to silver chloride is 1:2.5, react at 55°C for 1h, so that the silver chloride is reduced to nano-silver loaded on the titanium dioxide, and then centrifuge and wash with water to obtain primary modified titanium dioxide particles loaded with nano-silver;

[0085] 4) Disperse the prepared primary modified titanium dioxide particles in 4 times the mass of water, add polyethyleneimine, stir for 2 hours, then drop silane coupling agent 3-(triethoxysilyl)propyl methacrylate, stir for 3 hours, centrifuge, wash and dry to obtain composite modified titanium dioxide particles loaded with nanosilver, the amount of polyethyleneimine added is 5wt% of the primary modified titanium dioxide particles, and the amount of silane coupling agent added is 3wt% of the primary modified titanium dioxide particles;

[0086] Step b, firstly, 20 g of OPHB bio-based antibacterial stock solution and 40 g of ethanol were mixed to prepare solution A;

[0087] Step c, adding 50 g of the composite modified titanium dioxide particles loaded with nanosilver prepared in step a to 70 g of water, then adding 8 g of polyvinyl alcohol and 8 g of povidone, stirring and mixing, and then adding 15 g of hydroxypropyl β-cyclodextrin, and mixing to prepare solution B;

[0088] Step d, adding solution A to solution B, heating to 70° C., stirring and mixing, and then cooling to room temperature to obtain an antibacterial agent.

[0089] Preparation Example 4

[0090] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that: in step a (2), tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is added together with glutathione, and the added amount of tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is 0.05wt% of titanium dioxide.

[0091] Preparation Example 5

[0092] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that: in step a (2), tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is added together with glutathione, and the added amount of tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is 0.1wt% of titanium dioxide.

[0093] Preparation Example 6

[0094] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that in step a) 2), tetramethylammonium tetrafluoroborate is added together with glutathione, and the amount of tetramethylammonium tetrafluoroborate added is 0.1wt% of titanium dioxide.

[0095] Preparation Example 7

[0096] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that: in step a (2), glutathione is not added.

[0097] Preparation Example 8

[0098] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that in step a) 2), titanium dioxide is prepared by the following method:

[0099] Dissolving titanium tetrachloride and zinc chloride in water to obtain a mixed aqueous solution, and then adding the mixed aqueous solution into ammonia water to obtain a mixture having titanium dioxide colloidal particles, wherein the added mass ratio of titanium tetrachloride to zinc chloride is 1:0.4, and the mass concentration of titanium tetrachloride in the mixed aqueous solution is 25%, the amount of ammonia water added is 1.5 times the mass of titanium tetrachloride, and the mass concentration of ammonia water is 28%;

[0100] Then, PEO was added to the mixture and stirred to mix. The amount of PEO added was 4wt% of titanium tetrachloride. Then, the mixture was aged at 70°C for 36h. Then, the mixture was rinsed and dried with PBS phosphate buffer solution with a pH value of 7.3. Then, the mixture was calcined at high temperature. The high temperature calcination parameters were as follows:

[0101] First, the material is treated at 130°C for 30 minutes, then heated to 600°C and treated for 1.5 hours. Then, the material is heated to 780°C and treated for 2.5 hours. After that, the material is treated at 630°C for 1.5 hours, and then rapidly cooled (cooled to room temperature within 30 minutes) to obtain porous titanium dioxide.

[0102] Preparation Example 9

[0103] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that in step a) 2), titanium dioxide is prepared by the following method:

[0104] Dissolving titanium tetrachloride and zinc chloride in water to obtain a mixed aqueous solution, and then adding the mixed aqueous solution into ammonia water to obtain a mixture having titanium dioxide colloidal particles, wherein the added mass ratio of titanium tetrachloride to zinc chloride is 1:0.3, and the mass concentration of titanium tetrachloride in the mixed aqueous solution is 20%, and the amount of ammonia water added is 1 mass multiple of titanium tetrachloride, and the mass concentration of ammonia water is 28%;

[0105] Then, PEO was added to the mixture and stirred and mixed. The amount of PEO added was 3wt% of titanium tetrachloride. Then, the mixture was aged at 60°C for 48h. Then, the mixture was rinsed and dried with PBS phosphate buffer solution with a pH value of 7.3. Then, the mixture was calcined at high temperature. The high temperature calcination parameters were as follows:

[0106] First, the material is treated at 120°C for 40 minutes, then heated to 580°C and treated for 2 hours, then heated to 750°C and treated for 3 hours, and then treated at 620°C for 2 hours, and then quickly cooled (cooled to room temperature within 30 minutes) to obtain porous titanium dioxide.

[0107] Preparation Example 10

[0108] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that in step a) 2), titanium dioxide is prepared by the following method:

[0109] Dissolving titanium tetrachloride and zinc chloride in water to obtain a mixed aqueous solution, and then adding the mixed aqueous solution into ammonia water to obtain a mixture having titanium dioxide colloidal particles, wherein the added mass ratio of titanium tetrachloride to zinc chloride is 1:0.5, and the mass concentration of titanium tetrachloride in the mixed aqueous solution is 30%, and the amount of ammonia water added is 2 times the mass of titanium tetrachloride, and the mass concentration of ammonia water is 28%;

[0110] Then, PEO was added to the mixture and stirred and mixed. The amount of PEO added was 5wt% of titanium tetrachloride. Then, the mixture was aged at 80°C for 24h. Then, the mixture was rinsed and dried with PBS phosphate buffer solution with a pH value of 7.3. Then, the mixture was calcined at high temperature. The high temperature calcination parameters were:

[0111] First, the porous titanium dioxide was prepared by treating the sample at 140°C for 20 minutes, then heating to 620°C for 1 hour, then heating to 800°C for 2 hours, then treating the sample at 650°C for 1 hour, and then rapidly cooling the sample (cooling the sample to room temperature within 30 minutes).

[0112] Preparation Example 11

[0113] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 8, except that zinc chloride is not added to the raw materials.

[0114] Preparation Example 12

[0115] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 8, except that PEO is not added to the mixture and the mixture is directly aged.

[0116] Comparative Preparation Example 1

[0117] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that in step b, an equal amount of the OPHB bio-based antibacterial stock solution is replaced by composite modified titanium dioxide particles loaded with nanosilver.

[0118] Comparative Preparation Example 2

[0119] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that when preparing the composite modified titanium dioxide particles loaded with nanosilver in step a, step 4) treatment is not performed.

[0120] Comparative Preparation Example 3

[0121] A method for preparing an antibacterial agent is carried out according to the method in Preparation Example 1, except that when preparing the composite modified titanium dioxide particles loaded with nanosilver in step a, polyethyleneimine is not added in step 4), and only a silane coupling agent is added.

[0122] Example 1

[0123] A method for preparing a curtain fabric with antibacterial function comprises the following steps:

[0124] S1, using polyester fiber and cotton fiber in a mass ratio of 6:4 to blend to obtain a base fabric layer;

[0125] S2, the antibacterial agent prepared in Preparation Example 1 is applied on the surface of the base fabric layer, and then dried at 75°C to form an antibacterial layer, wherein the amount of the antibacterial agent applied is 2.2wt% of the antibacterial base fabric;

[0126] S3, laminating the side of the base fabric layer with the antibacterial layer to the pure cotton surface layer and hot-pressing them to obtain a curtain fabric with antibacterial function.

[0127] Example 2

[0128] A method for preparing a curtain fabric with antibacterial function comprises the following steps:

[0129] S1, using polyester fiber and cotton fiber in a mass ratio of 6:3 to blend to obtain a base fabric layer;

[0130] S2, the antibacterial agent prepared in Preparation Example 1 is applied on the surface of the base fabric layer, and then dried at 70°C to form an antibacterial layer, wherein the amount of the antibacterial agent applied is 1.5wt% of the antibacterial base fabric;

[0131] S3, laminating the side of the base fabric layer with the antibacterial layer to the pure cotton surface layer and hot-pressing them to obtain a curtain fabric with antibacterial function.

[0132] Example 3

[0133] A method for preparing a curtain fabric with antibacterial function comprises the following steps:

[0134] S1, using polyester fiber and cotton fiber in a mass ratio of 6:5 to blend to obtain a base fabric layer;

[0135] S2, the antibacterial agent prepared in Preparation Example 1 is applied on the surface of the base fabric layer, and then dried at 80°C to form an antibacterial layer, wherein the amount of the antibacterial agent applied is 3wt% of the antibacterial base fabric;

[0136] S3, laminating the side of the base fabric layer with the antibacterial layer to the pure cotton surface layer and hot-pressing them to obtain a curtain fabric with antibacterial function.

[0137] Embodiment 4-12

[0138] A method for preparing a curtain fabric with antibacterial function is carried out according to the method in Example 1, except that the antibacterial agent in step S2 is the antibacterial agent prepared in Preparation Examples 4-12.

[0139] Embodiment 13

[0140] A method for preparing a curtain fabric with antibacterial function is carried out according to the method in Example 1, except that:

[0141] In step S2, before applying the antibacterial agent to the base fabric layer, the base fabric layer is first immersed in the antibacterial liquid at a temperature of 55°C. The fabric residue rate after immersion is 45%, and then dried to obtain a pretreated base fabric layer. The antibacterial liquid includes a mixed solution of an antibacterial agent, sodium dodecylbenzene sulfonate, piroctone ethanolamine salt and water in a mass ratio of 1:0.1:2.5:9. The antibacterial agent is then applied to the pretreated base fabric layer to form an antibacterial layer.

[0142] Embodiment 14

[0143] A method for preparing a curtain fabric with antibacterial function is carried out according to the method in Example 1, except that:

[0144] In step S2, before applying the antibacterial agent to the base fabric layer, the base fabric layer is first immersed in the antibacterial liquid at a temperature of 50°C. The fabric residue rate after immersion is 45%, and then dried to obtain a pretreated base fabric layer. The antibacterial liquid includes a mixed solution of an antibacterial agent, sodium dodecylbenzene sulfonate, piroctone ethanolamine salt and water in a mass ratio of 1:0.1:2:8. The antibacterial agent is then applied to the pretreated base fabric layer to form an antibacterial layer.

[0145] Embodiment 15

[0146] A method for preparing a curtain fabric with antibacterial function is carried out according to the method in Example 1, except that:

[0147] In step S2, before applying the antibacterial agent to the base fabric layer, the base fabric layer is first immersed in the antibacterial liquid at a temperature of 60°C. The residual rate of the fabric after immersion is 50%. The pretreated base fabric layer is then dried to obtain the antibacterial agent, the antibacterial liquid comprising a mixed solution of an antibacterial agent, sodium dodecylbenzene sulfonate, piroctone ethanolamine salt and water in a mass ratio of 1:0.2:3:10. The antibacterial agent is then applied to the pretreated base fabric layer to form an antibacterial layer.

[0148] Comparative Examples 1-3

[0149] A method for preparing a curtain fabric with antibacterial function is carried out according to the method in Example 1, except that the antibacterial agent in step S2 is the antibacterial agent prepared in comparative preparation examples 1-3.

[0150] Performance Testing

[0151] Considering that the antibacterial agent has a good antibacterial effect on common bacteria Escherichia coli and Staphylococcus aureus, the present application first refers to GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method" to measure the antibacterial activity of Candida albicans on the curtain fabrics prepared in the examples and comparative examples of the present application. In addition, the curtain fabrics prepared in the examples and comparative examples of the present application were washed 20 times and then subjected to the above-mentioned antibacterial test. The reduction rate of the antibacterial rate before and after washing was statistically calculated. The test results are shown in Table 1 below.

[0152]

[0153] Referring to the test results in Table 1 above, it can be seen that the curtain fabric prepared in the present application has excellent antibacterial properties and antibacterial persistence. Combining the test results of Example 1 and Example 4-5, when nanosilver is loaded on titanium dioxide, when water-insoluble tetramethylammonium bistrifluoromethanesulfonyl imide salt ionic liquid is also added in Example 4-5, its antibacterial properties and antibacterial persistence are improved. Combined with the test results of Example 6, the antibacterial properties and antibacterial persistence of Example 5 in which a water-insoluble ionic liquid is added are better than those of Example 6 in which a water-soluble quaternary ammonium salt ionic liquid is added. This may be because the water-insoluble quaternary ammonium salt spicy chicken liquid is more easily adsorbed and embedded in the porous dioxide peptide, which is beneficial to its antibacterial and synergistic effect. Combined with the test results of Example 7, when nanosilver is loaded on titanium dioxide, when glutathione is not added, its antibacterial rate and antibacterial durability are also significantly reduced. The addition of glutathione helps to uniformly load nanosilver on porous titanium dioxide, thereby improving its antibacterial property and antibacterial durability.

[0154] Combined with the test results of Example 1 and Examples 8-10, when the titanium dioxide in this application is porous titanium dioxide doped with zinc oxide, its antibacterial persistence is further significantly improved. Referring to the results of Example 11, when the porous titanium dioxide is not doped with zinc chloride but is added with PEO, its antibacterial property is improved compared with Example 1, but weaker than the test results of Example 8. When PEO is not added in Example 12, its antibacterial persistence is improved compared with Example 1, but weaker than the test results of Example 8. It can be seen that the doping of zinc chloride helps to improve the antibacterial performance, and the addition of PEO helps to improve the antibacterial persistence for the construction of the pore structure. Combined with the test results of Examples 13-15, when the antibacterial agent is treated on the substrate by two methods, namely, impregnation and coating, its antibacterial persistence is significantly improved.

[0155] Combining the test results of Example 1 with those of Comparative Example 1, it can be seen that when only nanosilver composite-modified titanium dioxide particles are selected, the antibacterial effect is significantly reduced, and the antibacterial persistence is also reduced. Combined with the test results in Comparative Example 2, when titanium dioxide in Comparative Example 2 is only loaded with nanosilver but not modified with polyethyleneimine and silane coupling agent, its antibacterial persistence is significantly reduced, while when titanium dioxide in Comparative Example 3 is only modified with silane coupling agent, its antibacterial persistence is improved but still reduced.

[0156] In addition, the antibacterial properties of Escherichia coli and Staphylococcus aureus and the reduction rate of the antibacterial rate after washing 20 times were tested for the curtain fabrics in Examples 1, 4, 8, 13 of the present application and Comparative Examples 1-3 according to the above method. The test results are shown in Table 2 below. In addition, the air permeability test was carried out with reference to GB / T 5453-1997 "Determination of Air Permeability of Textile Fabrics", and the test results are shown in Table 2 below.

[0157]

[0158] Referring to the test results in Table 2 above, the curtain fabric prepared in the present application has excellent antibacterial properties as well as excellent antibacterial durability and air permeability.

[0159] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A curtain fabric with antibacterial function, characterized in that: The invention comprises a base fabric layer, an antibacterial layer and a surface layer, wherein the base fabric layer is formed by blending polyester fiber and cotton fiber, the antibacterial layer is formed by coating the surface of the base fabric layer with an antibacterial agent, and the base fabric layer is immersed in an antibacterial liquid before coating the antibacterial agent, wherein the antibacterial liquid comprises a mixed solution of an antibacterial agent, sodium dodecylbenzene sulfonate, piroctone olamine salt and water in a mass ratio of 1: (0.1-0.2): (2-3): (8-10); The antibacterial agent is prepared by the following method: Firstly, the OPHB bio-based antibacterial stock solution and ethanol are mixed to prepare solution A; Adding composite modified titanium dioxide particles loaded with nanosilver into water, then adding polyvinyl alcohol and povidone, stirring and mixing, and then adding hydroxypropyl β-cyclodextrin, and mixing to prepare solution B; Solution A is added to solution B, and the mixture is heated to 65-70°C, stirred and mixed, and then cooled to room temperature to prepare an antibacterial agent; The modified titanium dioxide particles are prepared by the following method: 1) Mixing silver chloride solution and polyvinyl pyrrolidone to prepare a matrix solution; 2) Add hydroxypropyl cellulose, glutathione and titanium dioxide to the base solution and stir to obtain a mixture A; 3) Adjust the pH value of the mixture A to be alkaline, and add glucose reducing agent to the mixture A, react at 45-55° C. for 1-3 hours, so that the silver chloride is reduced to nano-silver loaded on the titanium dioxide, and then centrifuge and wash with water to obtain primary modified titanium dioxide particles loaded with nano-silver; 4) Disperse the prepared primary modified titanium dioxide particles in 3-4 times the mass of water, add polyethyleneimine, stir for 1-2 hours, then dropwise add silane coupling agent, stir for 2-3 hours, centrifuge, wash with water and dry to obtain composite modified titanium dioxide particles loaded with nanosilver; The titanium dioxide is prepared by the following method: A mixed solution of titanium tetrachloride and zinc chloride is added into ammonia water to obtain titanium dioxide colloidal particles, and then PEO is added and stirred and mixed, and then aged at 60-80°C, and then washed with a buffer solution and dried, and then calcined at high temperature to obtain porous titanium dioxide.

2. The curtain fabric with antibacterial function according to claim 1, characterized in that: When preparing composite modified titanium dioxide particles loaded with nano-silver, the amount of polyvinyl pyrrolidone added in step 1) is 1-3wt% of the silver chloride solution, and the mass concentration of silver chloride is 45-50%; In step 2), the mass ratio of hydroxypropyl cellulose to glutathione is 1:(1.2-1.5), and the amount of hydroxypropyl cellulose added is 0.5-1.5wt% of the matrix solution, and the mass ratio of titanium dioxide to silver chloride added is 1:(1.5-2); In step 3), the mass ratio of glucose to silver chloride added is 1:(1.8-2.5); In step 4), the amount of polyethyleneimine added is 3-5wt% of the primary modified titanium dioxide particles, and the amount of silane coupling agent added is 1-3wt% of the primary modified titanium dioxide particles.

3. The curtain fabric with antibacterial function according to claim 1, characterized in that: When preparing composite modified titanium dioxide particles loaded with nanosilver, tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is added together with glutathione, and the added amount of tetramethylammonium bis(trifluoromethanesulfonyl)imide salt is 0.05-0.1wt% of titanium dioxide.

4. The curtain fabric with antibacterial function according to claim 1, characterized in that: When preparing titanium dioxide, the added mass ratio of titanium tetrachloride to zinc chloride is 1:(0.3-0.5), the mass concentration of titanium tetrachloride is 20-30%, and the amount of ammonia added is 1-2 times the mass of titanium tetrachloride, and the amount of PEO added is 3-5wt% of titanium tetrachloride.

5. The curtain fabric with antibacterial function according to claim 1, characterized in that: During the preparation of the antibacterial agent, each raw material is added according to the following weight parts: 10-20 parts of OPHB bio-based antibacterial stock solution, 40-50 parts of composite modified titanium dioxide particles loaded with nano-silver, 5-8 parts of polyvinyl alcohol, 3-8 parts of povidone, 8-15 parts of hydroxypropyl beta-cyclodextrin, 30-40 parts of ethanol, and 50-70 parts of water.

6. A method for preparing a curtain fabric with antibacterial function according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1, blending polyester fiber and cotton fiber in a mass ratio of 6:(3-5) to obtain a base fabric layer; S2, applying an antibacterial agent on the surface of the base fabric layer, and then drying to form an antibacterial layer, wherein the amount of the antibacterial agent applied is 1.5-3wt% of the antibacterial base fabric; S3, laminating the side of the base fabric layer with the antibacterial layer to the surface layer and hot-pressing them to obtain a curtain fabric with antibacterial function.

Citation Information

Patent Citations

  • Bio-based material with antibacterial effect and application thereof

    CN110452121A

  • Antibacterial garment material and preparation method thereof

    CN113684677A

  • Tear-resistant antibacterial non-woven fabric and preparation method thereof

    CN115012210A

  • KR1025137530000B1